Development of Static Fluid Practicum Modules in the Independent Curriculum to Improve Student Learning Outcomes - Chanthika Putri; Yuni Warty (JURNAL PENDIDIKAN MIPA, 2024)
Teaching materials available in the field are still minimal and need to be developed. To enhance a more directed learning process, improve student learning outcomes, and increase student independence in learning, it is necessary to develop teaching materials for an independent curriculum. This research aims to develop a scientific-based static fluid practicum module of the independent curriculum. The type of research used is the Research and Development (R&D) using the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. Data collection techniques were feasibility questionnaire, practicality questionnaire and multiple-choice questions for pre-test and post-test. The results of the analysis show that students lack direct observation in learning due to the unavailability of teaching materials that support practicum activities. This research data shows the percentage of the feasibility level of the practicum module which obtained an average of 92.2%, the practicality level of the practicum module obtained an average of 89.9% and the effectiveness level of the practicum module obtained an N-Gain of 0.70. The developed practicum module is feasible, practical, and effective in learning high school physics.